Education Management at the Jekdong Puppet Performance in Malang - Astrid Wangsagirindra Pudjastawa; Yudit Perdananto (Universitas Hamzanwadi, 2022)
The purpose of this study was to describe the management process of Wayang Jekdong performances in Malang as a form of management education from a puppeteer in managing and leading Wayang Jekdong. Researchers are a key instrument in collecting data by going to the field. The research method used is a descriptive qualitative approach by conducting observations, interviews, and documentation. The data analysis technique of this research uses the Miles and Huberman model by reducing, presenting, and verifying the data found. The results showed that there were several stages of management carried out by the puppeteer in the Wayang Jekdong show, namely: planning, forecasting, organizing, personnel, directing, implementing, coordinating, leadership, motivating, and supervising. A puppeteer must be able to apply management knowledge properly in order to perform smoothly in sequence according to plan, to satisfy the audience.